Induksi Tunas dari Eksplan Nodus Jeruk Kasturi (Citrus microcarpa Bunge.) dengan Penambahan 6- Benzyl Amino Purine (BAP) Secara In Vitro: INDUKSI TUNAS DARI EKSPLAN NODUS JERUK KASTURI (CITRUS MICROCARPA BUNGE.) DENGAN PENAMBAHAN 6- BENZYL AMINO PURINE (BAP) SECARA IN VITRO - Yanti, Defila; Novaliza Isda, Mayta (Biospecies, 2021)
Kasturi orange (Citrus microcarpa Bunge.) is a medicinal plant that contains chemical compounds from secondary metabolites. Limitations of the seed and slow rate of growth is a challenge in the Kasturi orange plant propagation. Propagation of shoots in the kasturi orange can be produced quickly with shoots induction in vitro. This study aims investigate the influence and determine the concentration of BAP in inducing shoots from nodes kasturi orange explants in vitro. This research was conducted at the Integrated Laboratory, Department of Biology, Faculty of Mathematics and Natural Sciences, The University of Riau from March - September 2020 using completely randomized design (CRD) which consists of 6 (six) treatments than is control BAP (1,2,3,4,5 mg / L). Results showed BAP had a significantly affect the number of shoots and shoot length. The treatment of 1 mg / L BAP produces the highest number of shoots that 2.50. The highest callus growth was in the treatment of 5 mg / L BAP. The shoot appears fastest time is 12.00 day after planting (DAP) contained in the treatment of 2 mg/L BAP.